DETERMINAN MINAT STUDI LANJUT KE PERGURUAN TINGGI SISWA SMK BEZAB KECAMATAN KWANYAR KABUPATEN BANGKALAN - Yusrianto Sholeh; Bagus Setiawan (Jurnal Manajemen Pendidikan, 2026)
This research is based on students' interest in deciding to study at university. Various studies show that students' interest in studying at university is still low, there are several major considerations related to the decision to continue studying or not. Bani Zainal Abidin Islamic Boarding School is a non-formal Islamic institution located in Kwanyar District, Bangkalan Regency. There are 4 major categories: Career considerations, school achievements, social environment, and internal decisions. This study uses an associative quantitative approach to examine the influence of four factors on the interest of SMK Bezab students to continue their studies. The sample was selected purposively. Variables were measured through a 1–5 Likert scale questionnaire and analyzed using multiple linear regression or ordinal logistic regression. The results show that partially, all independent variables, namely job prospect considerations (X1), academic achievement (X2), social influence (X3), and decision-making process (X4) have a significant effect on students' interest in continuing their studies at university (Y), with each calculated t value greater than the t table (X1 = 10.389; X2 = 6.194; X3 = -4.567). Simultaneously, the four factors also have a significant effect (F count = 217.959>F table = 2.77; p = 0.000), with a contribution of 92% (R² = 0.92).